Utilization of remote sensing and population dynamics for predicting the annual generations of cotton leafworm spodoptera littoralis (boisd.) (lepidoptera: noctuidae) under climate change - Amira Hassan Ahmed Moursey; Hassan Farag Dahi; Ibtisam Abdelmoneim Hemeida; Sayeda Sayed Ahmed (Cairo : Amira Hassan Ahmed Moursey, 2014)
This study was conducted to study the effect of four constant temperatures 17, 22, 27 and 32 {u00B0}C on the biology of cotton leafworm, Spodoptera littoralis and determine the threshold temperature and calculation of the thermal units for all stages in laboratory to determine the threshold temperature and the average number of degree days demanded for complete one generation then used both information for predicting annual generations of S. littoralis under field condition
Thesis (M.Sc.) - Cairo University - Faculty of Agriculture - Department of Economic Entomology and Pesticides
Issued also as CD
Keywords: Accumulate heat units; NOAA satellite image; Spodoptera littoralis generations